Pengaruh Financial Distress, Reputasi Auditor Dan Solvabilitas Terhadap Nilai Perusahaan Dengan Kualitas Audit Sebagai Variabel Moderasi - Sysilia Tri Hapsari; Nera Marinda Machdar (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
In the last few decades, the Indonesian capital market has developed rapidly and become increasingly complex. The market experiences various changes and challenges. Businesses listed on the Indonesian Stock Exchange are affected by high share price changes, changes in exchange rates, and national and international economic downturns. Manufacturing companies in Indonesia, which is a major economic sector, face great pressure to maintain and increase the value of their business amidst ongoing economic changes.